Safety of Human Papillomavirus 9-Valent Vaccine: A Meta-Analysis of Randomized Trials. (24th July 2017) - Costa, Ana Paula Ferreira; Cobucci, Ricardo Ney Oliveira; da Silva, Janine Medeiros; da Costa Lima, Paulo Henrique; Giraldo, Paulo César; Gonçalves, Ana Katherine
Abstract : Vaccination against human papillomavirus (HPV) has been progressively implemented in most developed countries for approximately 10 years. In order to increase the protection of the vaccines, a 9-valent vaccine (HPV9) was developed, which provides protection against nine types of the virus. Studies evaluating its safety are rare. Thus, we performed a meta-analysis of three clinical trials assessing adverse effects on women randomly vaccinated with HPV9 or tetravalent vaccine (HPV4), with the objective of analyzing whether the HPV9 is as safe as HPV4. An electronic data search was performed through the PubMed, Embase, Scopus, Web of Science, and SciELO databases. The studies selected 27, 465 women who received one of the two vaccines. Pain (OR 1.72; 95% CI 1.62–1.82) and erythema (OR 1.29; 95% CI 1.21–1.36) occurred significantly more in the HPV9 group. However, there was no significant difference between the groups for the following adverse effects: headache (OR 1.07; 95% CI 0.99–1.15), dizziness (OR 1.09; 95% CI 0.93–1.27), and fatigue (OR 1.09; 95% CI 0.91–1.30), and the occurrence of serious events related to vaccination was similarly rare among those vaccinated. Therefore, our findings demonstrate that HPV9 in female patients is as safe as the tetravalent vaccine.